A Proposed Strategy to Develop Postgraduate Studies at King Khalid University to Support the Achievement of the Kingdom's 2030 Vision (Journal Of Educational and Psychological Researches, 2023)
AbstractThe aim of this research is to formulate a proposed strategy for developing graduate studies at King Khalid University to support the achievement of the Kingdom's vision (2030). The research used the descriptive survey approach. The research community consisted of all graduate students at King Khalid University. The research was conducted on a random sample included (623) Male and female students, this research relied on the questionnaire as the main tool for collecting its data. The results revealed that the research sample believes that all the proposals included in this research are very important for the development of postgraduate studies at King Khalid University to support the achievement of the Kingdom's vision (2030). There are no statistically significant differences between the averages of the research sample responses about the importance of the proposals put forward in this research according to their difference in the two variables: college and gender, while these differences were found according to their difference in the academic program variable in favor of students enrolled in the master's program. The research presented a formulation of a proposed strategy for developing graduate studies at King Khalid University in a way that supports the achievement of the Kingdom's vision (2030).